Examining Financial Governance Practices in Islamic Boarding Schools: Managing Education Funds in Palangka Raya - Harmini; Ibnu Elmi AS Pelu (Center for Studies in Advanced Science, 2026)
The management of educational funds in Islamic boarding schools (pesantren) faces increasing demands for transparency, accountability, and sustainability in educational operations. However, many pesantren still rely on informal financial management practices that limit effective governance. This study aims to examine the implementation of good financial governance principles in managing educational funds in Islamic boarding schools in Palangka Raya and to analyze their implications for educational quality. The research employed a qualitative case study design involving several pesantren in Palangka Raya. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using thematic qualitative analysis. The findings reveal that fund management in many pesantren is still dominated by traditional and trust-based practices, characterized by the absence of formal financial planning documents, limited transparency mechanisms, weak administrative accountability, and inadequate financial management capacity among administrators. Pesantren that adopt more structured financial governance practices demonstrate better allocation of resources, improved educational facilities, and more sustainable learning programs. This study contributes to the literature on Islamic education management by providing empirical evidence on how good financial governance can strengthen institutional accountability and support the improvement of educational quality in pesantren.